The level of relatedness affects self/nonself discrimination in Eucalyptus urophylla seedlings - Bertoli, Suzana Chiari; Neris, Daniel Moreira; Sala, Helida Regina; Vieira, Willyam De Lima [UNESP]; Souza, Gustavo Maia (Canadian Science Publishing, 2020)
Plants can develop differentially because of their ability of self/nonself discrimination and the degree of kinship among them. Here, we evaluate the ability of self/nonself discrimination of Eucalyptus urophylla S.T. Blake roots in plant groups with different levels of relatedness. We used three plant groups: clonal, half-siblings, and population. Split-root plants were grown in pots containing either two roots of the same plant (S-D) or of two different plants (NSD). The growth of root and leaves of the half-siblings and population plants was decreased in NSD in relation to S-D, whereas this response was not observed in the clonal group. The multivariate analysis indicated that there was a progressive increase in plant responses likely caused by competitive interaction of roots, as the level of relatedness between individuals was lower. Our results suggest that the group of clonal plants minimized the competitive interaction among them, indicating low ability to discriminate from each other. However, half-sibling and populational plants reduced growth as a result of root competition, showing high capacity of self discrimination. Thus, a minimum degree of genetic variation between plants seems necessary for kin recognition to be expressed.
Keywords: competition; kin recognition; principal component analysis; root interaction; self/nonself discrimination